Critical Involvement of CD44 in T Helper Type 2 Cell-Mediated Eosinophilic Airway Inflammation in a Mouse Model of Acute Asthma - Katoh, Shigeki (Frontiers in Immunology, 2022)
Interactions between CD44 and hyaluronan (HA) are crucial for recruiting leukocytes to inflamed tissues. This review summarizes findings from our studies of the roles of CD44-HA interactions in leukocyte trafficking, with a particular focus on airway T helper type 2 (Th2) cells in mouse models of acute asthma. In a mite allergen-induced model of acute asthma, intraperitoneal injection of anti-CD44 monoclonal antibodies blocked lymphocytes and eosinophils from accumulating in the lung, and suppressed both the antigen-induced increase in Th2 cytokines in the bronchoalveolar lavage fluid (BALF) and airway hyperresponsiveness (AHR). CD44 deficiency was associated with decreased mite allergen-induced Th2 cell-mediated airway inflammation and AHR in sensitized mice. Asthmatic responses to antigen-sensitized splenic CD4+ T cells transferred from CD44-deficient mice were weaker than in wild-type mice. Administration of anti-CD44 monoclonal antibodies preferentially suppressed the airway accumulation of antigen-specific Th2 cells induced by antigen challenge, without affecting Th1 and Th17 cells. Increased HA-binding ability of CD44 and expression of Neu1 sialidase were observed on antigen-specific Th2 cells compared with antigen-specific Th1 and Th17 cells. Finally, in a mouse model of acute asthma, neuraminidase 1-deficient SM/J mice exhibited a lower Th2 cytokine concentration and a lower absolute Th2 cell number in the BALF, as well as an attenuated AHR. Our findings indicate that CD44 critically contributes to the antigen challenge-induced airway accumulation of antigen-specific Th2 cells, without affecting Th1 and Th17 cells, in mice. Furthermore, neuraminidase 1 activity is necessary for the interaction between HA and CD44, and Th2 cell-mediated airway inflammation.